Privacy-Preserving Data Migration Techniques for Enterprise Databases - Solomon Raju Chigurupati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines privacy-preserving techniques for enterprise database migrations, particularly in healthcare and financial sectors where sensitive data requires stringent protection. It explores advanced methodologies including encryption approaches, tokenization strategies, and differential privacy implementations that organizations can deploy to safeguard information during system transitions. The work analyzes the regulatory landscape governing data migrations across jurisdictions, highlighting the complexities of cross-border transfers and data sovereignty requirements. Beyond compliance considerations, the article demonstrates how secure migrations contribute to societal trust, enhancing relationships with patients and customers while creating competitive advantages. Through detailed examination of implementation strategies and architectural patterns, it provides practical recommendations for organizations seeking to balance robust privacy protections with operational efficiency, positioning privacy-preserving migrations as essential components of responsible data stewardship in an increasingly interconnected digital ecosystem.